Provisioning and nest success of an aerial insectivore at a high elevation breeding site - Simons, Victoria F., author; Horton, Kyle G., advisor; Doherty, Paul F., Jr., committee member; Ruegg, Kristen C., committee member (Colorado State University. Libraries, 2023)
Tree Swallows (Tachycineta bicolor) are a model organism in ornithology. However, few studies have been conducted in the western portion of their breeding range, particularly at high elevation. High elevation habitats, like Colorado State University's Mountain Campus, are impacted by climate change. Tree Swallows in these ecosystems face threats due to recent population declines and climate-related changes. These challenges could impact the species' survival in these areas, and for my Master's thesis I investigated two aspects of provisioning behavior, namely weather conditions and insect abundance. My first chapter focused on how daily weather conditions influenced female Tree Swallow's rates of nest visitation and food provisioning. Using radio-frequency identification technology, I compared visitation rates to hourly weather conditions. I found that poor weather, including cooler temperatures and precipitation events, was negatively correlated with the number of visits made to the nest, which subsequently influenced the growth and development of nestlings. In Chapter 2, I addressed the question of how weather affected food availability. Tree Swallows rely on flying insects as their main food source, and inclement weather is known to decrease insect availability in the airspace. To investigate if lowered female provisioning effort matched periods of food unavailability, I deployed a mobile radar unit – the BirdScan MR1 – to quantify insect abundance. I then compared insect activity to nest visitation rates and found that females made significantly more visits to their nestlings when insects were more abundant. Additionally, I found that insect activity was significantly influenced by weather conditions, demonstrating that weather may be used as a proxy for insect abundance at sites where direct monitoring of insects is not possible. Put together, the results of my first and second chapters deepen our understanding of how female Tree Swallows navigate the complexities of aerial conditions – both biotic and abiotic – to forage and provision for their growing nestlings in an ever-changing high elevation environment. As the effects of climate change become more pronounced, high elevation habitats are likely to undergo rapid changes. Consequently, insight into the relationship between weather and food availability becomes increasingly important.
Keywords: high elevation; provisioning behavior; tree swallows; insects; aeroecology; radar